Alterations of Cerebral Blood Flow and Its Connectivity in Olfactory-Related Brain Regions of Type 2 Diabetes Mellitus Patients - Luo, Wei; Wang, Jie; Chen, Mimi; Zhou, Shanlei; Deng, Datong; Liu, Fujun; Yu, Yongqiang (Frontiers in Neuroscience, 2022)
To investigate the alteration of cerebral blood flow (CBF) and its connectivity patterns in olfactory-related regions of type 2 diabetes mellitus (T2DM) patients using arterial spin labeling (ASL). Sixty-nine patients with T2DM and 63 healthy controls (HCs) underwent ASL scanning using 3.0T magnetic resonance imaging. We compared the CBF values of the olfactory-related brain regions between the two groups and analyzed the correlation between their changes and clinical variables. We also used these regions as seeds to explore the differences in CBF connectivity patterns in olfactory-related brain regions between the T2DM patients and HCs. Compared with the HC group, the CBF of the right orbital part of the inferior frontal gyrus (OIFG), right insula, and bilateral olfactory cortex was decreased in the T2DM patients. Moreover, the duration of the patients was negatively correlated with the CBF changes in the right OIFG, right insula, and right olfactory cortex. The CBF changes in the right OIFG were positively correlated with the Self-Rating Depression Scale scores, those in the right insula were negatively correlated with the max blood glucose of continuous glucose, and those in the right olfactory cortex were negatively correlated with the mean blood glucose of continuous glucose. In addition, the T2DM patients also showed decreased CBF connectivity between the right OIFG and the left temporal pole of the middle temporal gyrus and increased CBF connectivity between the right medial orbital part of the superior frontal gyrus and the right orbital part of the superior frontal gyrus and between the right olfactory cortex and the bilateral caudate and the left putamen. Patients with T2DM have decreased CBF and altered CBF connectivity in multiple olfactory-related brain regions. These changes may help explain why olfactory dysfunction occurs in patients with T2DM, thus providing insights into the neuropathological mechanism of olfactory dysfunction and cognitive decline in T2DM patients.